Introduction and overview [in Agricultural commercialization, economic development, and nutrition] - von Braun, Joachim (International Food Policy Research Institute, 1994)
Why should there be a book about the commercialization of subsistence agriculture, economic development, and nutrition? There are two compelling resasons. First, concerns and suspicions about adverse effects on the poor of commercialization of subsistence agriculture persist and influence policy of developing countries and of donor agencies. Second, in rural areas of low-income countries, nutritional welfare is determined by many complex factors whose relationships to agricultural commercialization and economic development need to be traced in order to design optimal rural growth policies that benefit the poor.